1986
DOI: 10.1089/hyb.1986.5.199
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Binding Activity Observed Between Anti-Carcinoembryonic Monoclonal Antibodies

Abstract: Six anti-carcinoembryonic monoclonal antibodies (CEA MAbs) were isolated and characterized. Through blocking studies, only two were found to share the same epitope, indicating that CEA has at least five different epitopic sites. One of the group, 31C5A4 was found to enhance greatly the binding of CEA by 20C2H1. When (31C5A4) was fragmented, both the F(ab')2 and Fab bound CEA and blocked the binding of CEA by intact 31C5A4; however, only F(ab')2 was able to enhance. Fab could be induced to enhance after being r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The central feature of this assay first takes advantage of the fact that a bivalent IgG molecule can bind in cyclic manner to a multivalent antigen (63,64), producing a stable complex containing one or two IgG molecules per p53 tetramer (59). Previous biochemical studies have also indicated that the number of antibodies bound to one tetrameric p53-DNA complex can be quantitated by counting the integral number of stable, intermediate IgGp53-DNA complexes separated by native gel electrophoresis (59).…”
Section: The Development Of An Immunochemical Assay To Quantitate In mentioning
confidence: 99%
“…The central feature of this assay first takes advantage of the fact that a bivalent IgG molecule can bind in cyclic manner to a multivalent antigen (63,64), producing a stable complex containing one or two IgG molecules per p53 tetramer (59). Previous biochemical studies have also indicated that the number of antibodies bound to one tetrameric p53-DNA complex can be quantitated by counting the integral number of stable, intermediate IgGp53-DNA complexes separated by native gel electrophoresis (59).…”
Section: The Development Of An Immunochemical Assay To Quantitate In mentioning
confidence: 99%
“…Polyclonal antisera produced by rabbits immunized with protein conjugates of either l -thyroxine or 3,5,3‘-triiodo- l -thyronine were reported to bind the corresponding soluble antigens with a high degree of positive cooperativity. In contrast to the scarcity of literature on allosteric effects due to antigen binding-dependent conformation changes in the antibody, many laboratories have reported that protein antigens can display positive cooperativity in the binding of multiple antibodies to different epitopes on the antigen ( ). In each of these latter examples, however, the positive cooperativity was thought to arise either from conformation changes in the protein antigen that occurred as a consequence of antibody binding ( ), or from cyclic structures that could form as a consequence of the multivalency of both the antibody and the protein antigen ( ).…”
mentioning
confidence: 99%
“…In contrast to the scarcity of literature on allosteric effects due to antigen binding-dependent conformation changes in the antibody, many laboratories have reported that protein antigens can display positive cooperativity in the binding of multiple antibodies to different epitopes on the antigen ( ). In each of these latter examples, however, the positive cooperativity was thought to arise either from conformation changes in the protein antigen that occurred as a consequence of antibody binding ( ), or from cyclic structures that could form as a consequence of the multivalency of both the antibody and the protein antigen ( ). In either case, binding-induced conformation changes in the antibodies were neither postulated nor required to rationalize the experimental observations.…”
mentioning
confidence: 99%
“…In contrast, studies using two MAbs with high individual in vivo localization indices for xenografts of colon carcinoma (in nude mice) gave significantly enhanced labelling indices when both were injected together (Munz et al, 1986). MAbs against certain epitopes on carcinoembryonic antigen (CEA) were also shown to increase binding of MAb to other epitopes (Wellerson and Kaplan, 1986). It is evident from these studies that the use of MAb cocktails needs to be assessed for individual tumours but that the presence of two MAbs with high individual labelling indices may be superior to either alone.…”
Section: Mabs Against Tumour-associated Antigens On Melanoma Cells-anmentioning
confidence: 99%